Morbidity, mortality and cost from HPV-related oropharyngeal cancer: Impact of 2-, 4- and 9-valent vaccines. Issue 6 (2nd June 2016) - Ward, Greg; Mehta, Vikas; Moore, Michael
ABSTRACT: Objective: The incidence of oropharyngeal squamous cell carcinoma (OPSCC) related to human papillomavirus (HPV) is increasing at a dramatic rate, with men affected more commonly than women. Individuals who develop this disease suffer significant morbidity and potential mortality from their cancer and its associated treatment. We aim to evaluate the possible impact that the currently available HPV vaccines will have on this group of cancers. Data sources: Available peer-reviewed literature, practice guidelines, and statistics published by the Center for Disease Control and Prevention. Review methods: Contemporary peer-reviewed medical literature was selected based on its scientific validity and relevance to the impact HPV vaccination may have on the morbidity, mortality and cost resulting from HPV-related OPSCC in the United States. Conclusions: The incidence of HPV-related OPSCC is increasing at a near epidemic rate in the United States. The cost of treatment of HPV-related OPSCC is high, and the disease and its therapy result in significant morbidity and potential mortality to individuals. Using a cut-off of 50, 000/Quality-Adjusted Life Year, expansion of current HPV vaccine indications to include prevention of OPSCC in both men and women should be recommended.